Arahan Pengembangan Infrastruktur Drainase Berbasis Sistem Informasi Geografis - Muh Fadel; Muh Yamin Jinca; Muh Fathien Azmy (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
Drainage is one of the basic infrastructure which is an important component in urban planning. This study aims to determine the condition of existing drainage, identify the location of inundation, and arrange direction for drainage infrastructure development in Lappa Village. Data collection is done through direct observation, interviews, documentation and literature studies. The analytical methods used include, hydrological analysis, descriptive qualitative and quantitative, and geographical analysis using ArcGis 10.4 software. The results of this study indicate that there are 2 out of a total of 17 overflowing drainage on Jalan Sunu and Squid. Furthermore, the results of the comparative discharge plan and excisiting there are 6 drainage networks that are not able to accommodate the flow of water which will eventually cause inundation. The efforts made to improve the performance of the drainage network system are structuring a structured maintenance operation system so that maintenance operations are carried out regularly, forming a drainage management institution so that authority and responsibility can be coordinated in a directed manner and making clear management system regulations.